Wearable biofeedback improves human-robot compliance during ankle-foot exoskeleton-assisted gait training: a pre-post controlled study in healthy participants - Pinheiro, Cristiana (2020)
Supplementary material available at: https://www.mdpi.com/1424-8220/20/20/5876/s1